Anatomical Parameters of The Nasolacrimal Duct in Children Up West Measured with Computed Tomography - Upadhyay, Nikita; Bisht, Amit (Journal of Neonatal Surgery, 2025)
The nasolacrimal duct (NLD) plays a crucial role in tear drainage from the ocular surface to the nasal cavity, and its anatomical variations in children are of significant clinical relevance, particularly in the context of congenital nasolacrimal duct obstruction (CNLDO). This study aims to evaluate the normative anatomical parameters of the NLD in the pediatric population using high-resolution imaging modalities, including multidetector computed tomography (MDCT) and magnetic resonance imaging (MRI). Key parameters assessed include NLD length, diameter, angulation, and the morphology of the nasolacrimal canal. A retrospective analysis was conducted on imaging data from paediatric patients aged 0–20 years who underwent head CT scans for non-lacrimal indications. The NLD was visualized in axial and sagittal planes, and measurements were stratified by age and gender. The study revealed that NLD length and diameter increased progressively with age, with statistically significant differences noted between age groups. No significant gender differences were found in most parameters. The angle of the NLD relative to the nasal floor was also found to vary slightly with age, which may potentially influence tear flow dynamics. These findings establish normative reference values for NLD dimensions in children and enhance understanding of age-related anatomical development. The data have important implications for the diagnosis and management of CNLDO and for planning pediatric dacryocystorhinostomy (DCR) procedures. Further prospective studies with larger cohorts are recommended to validate these findings and explore ethnic or population-based variations.